(untitled) (Conferencea, 2023)
In order to effectively organize educational processes in our country, the use of advanced technologies, creation of electronic information educational resources, electronic textbooks, general requireфments for their creation, advantages and differences of electronic textbooks from traditional textbooks are highlighted in the article.